Optimalisasi Penggunaan Media Sosial dalam Promosi Pariwisata Pulau Untung Jawa - Lasmery RM Girsang; Ilona V.O Situmeang; William Althur (Universitas Tarakanita, 2025)
Not all tourist destinations in the Seribu Islands are considered having no obstacles. Among various islands, one of them is Untung Jawa Island which still improves. In fact, the condition of tourist destinations on Untung Jawa Island has kept great potency but has not been managed optimally yet. This was caused by some factors, one of them was less promotion effort carried out by tour guides on the island. Therefore, on December 17, 2024, the community service team conducted sharing and training for participants from